Implementation Of The Evaluation Of Learning From The Book "Ta'lÄ«m Muta'allim" In Fostering Tolerance Attitudes In The Educational Unit Of Muadalah Ulya Al Amiriyah School At Darussalam Islamic Boarding School, Tegalsari, Banyuwangi - M Afif Rosyidi Rifandi; Dyah Nawangsari; Saihan (Lingua: Jurnal Bahasa, Sastra dan Pengajarannya)
The learning process must involve many parties, which are balanced by technological developments to make it easier to achieve a certain atmosphere in the learning process so that students are comfortable in learning. Learning evaluation itself is carried out to determine the extent of students' knowledge, here evaluation is in a narrow sense. Meanwhile, in a broader sense, learning evaluation itself measures the level of success and failure of a learning process in achieving an expected educational goal. The book Ta'lim al-Muta'allim, namely the cultivation of santri learning ethics is a necessity in the world of learning, because with santri learning ethics participants can study well, in relation to the problem of santri learning ethics, there are three things, namely: about science, procedures for obtaining knowledge, various attitudes carried out by educators in seeking knowledge. Humans are social creatures who always interact with other individuals in order to fulfill their needs. TasÄmuá¸¥ behavior is one of the characteristics that a person can carry out as an answer to how to deal with the differences that exist in humans. TasÄmuá¸¥ behavior should be applied in everyday life so that harmony can be created both in family life, society, and national and state life. This attitude must also be instilled in children and students in the learning process, so that they are able to internalize this attitude in his life. The Mujadi Education Unit (SPM) Ulya Al-Amiriyyah is a school with an increasing percentage of students entering every year and has experienced good progress in a short period of time. SPM Ulya is a formal education unit at the same level as MA, SMA or SMK which is a branch of formal education at Madrasah Diniyah Al-Amiriyyah Darussalam.